(untitled) (Training and Practice : Journal of Educational Sciences, 2020)
In recent decades, the spread of information technology has significantly reshaped our world, opening up opportunities in both everyday life and education that we could not have imagined before. In the course of the year 2020 COVID-19 epidemic, the society was able to take advantage of the opportunities offered by IT in online communication, home office and digital education. But these possibilities are not taken for granted, we must learn to take advantage of them. Excessive adherence to the usual solutions and bureaucracy, in the ordinary sense, can lead to unnecessary extra work and administration. This year, the advantages and disadvantages of digital education were also experienced by the participants of the education system. If this knowledge were used wisely, traditional education could become much easier. That is the reason why I considered it necessary to conduct research to find out how students lived through this new situation: which courses went smoothly, what they think about the services they have used and how useful they have felt them.